2014
DOI: 10.1007/s12134-014-0406-9
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of the Second Generation: Evidence from a Field Experiment in Norway

Abstract: A major question in labour market research is the extent to which discrimination in employments causes the disadvantages experienced by children of immigrants. This article contributes to the debate by utilising a correspondence test study in which pairs of equivalent résumés and cover letters-one with a Pakistani name and one with a Norwegian name-were sent in response to 900 job openings in the greater Oslo area. The results show that applicants with Norwegian names on average are 25 % more likely to receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 52 publications
(62 reference statements)
4
82
0
14
Order By: Relevance
“…Second, future studies should evaluate how criminal background interacts with other individual traits, especially those that are known to have a negative impact on people's employability. We know, for example, that immigrants are discriminated against in the labor market in most European countries (see, e.g., Baert et al 2017;Baert and Vujić 2016;Carlsson and Rooth 2007;Midtbøen 2016). Do immigrants with a criminal background then face a double penalty in the hiring situation?…”
Section: Discussionmentioning
confidence: 99%
“…Second, future studies should evaluate how criminal background interacts with other individual traits, especially those that are known to have a negative impact on people's employability. We know, for example, that immigrants are discriminated against in the labor market in most European countries (see, e.g., Baert et al 2017;Baert and Vujić 2016;Carlsson and Rooth 2007;Midtbøen 2016). Do immigrants with a criminal background then face a double penalty in the hiring situation?…”
Section: Discussionmentioning
confidence: 99%
“…In several studies using correspondence tests it is suggested that discrimination is higher in private companies and that the chances of minority applicants to be invited for a job interview are greater in public companies (e.g. Wood et al 2009, Eid 2012, Midtbøen 2014. Our analysis confirms the assumption that public employers are less likely to discriminate against minority applicants, with the mean call back rate for private employers at 1.65, and a corresponding call back rate for the public sector at 1.19.…”
Section: Notes: N Indicates the Number Of Cases Includedmentioning
confidence: 99%
“…As with the email addresses discussed above it is, however, not possible to provide employers with this confirmation without openly lying. To my knowledge there are only two correspondence tests that made use of online application forms, which are Wood et al (2009) andMidtbøen (2014a).…”
Section: Constructing Contact Details For Fictitious Applicants -Legamentioning
confidence: 99%